Potential of brown macroalgae as a functional food in promoting antioxidant and hypocholesterolemic activities - Carrasqueira, Joana Filipa Ponte (2023)
Brown macroalgae are nutritionally rich, being composed of polysaccharides (such as fucoidan, laminaran, and alginate), carotenoids (e.g. fucoxanthin), and phenolic compounds (e.g. phlorotannins). Thus, brown macroalgae prove to be a promising product that promotes multiple beneficial health effects, such as hypocholesterolemia. In this study, extractions of the algae Fucus spp., Bifurcaria bifurcata, and Undaria pinnatifida were executed by using different solvents. The higher yield extracts were the aqueous ones, with approximately 30 %. Afterwards, these extracts were precipitated in order to obtain fractions rich in different sugars, and it was concluded that Fucus was richer in fucoidans, B. bifurcata had a similar content, whereas U. pinnatifida was in its majority made of alginate. The sample that had the highest content in chlorophylls a and b was Fucus spp. extracted with ethanol. Regarding the phlorotannins quantification, acetone revealed itself as the most efficient solvent for their extraction, being the B. bifurcata extracted with acetone the one with the highest concentration, of 21.8 ± 1.9 mg EPG/ g dry sample. The extract that was reported to have the highest antioxidant activity was B. bifurcaria in ethyl acetate, in both assays. The hypocholesterolemic activity analysis was made through the Kit Liquick Cor Chol 60, and the sample B. bifurcaria after the column C18 and rich in phenolic compounds was the one that presented the most promising results. Certain extracts rich in chlorophylls, and with antioxidant and hypocholesterolemic activity were chosen to be incorporated into guacamole, and their colour and rheology were then analysed. It was reported that the guacamole control oxidized faster than the remaining ones containing algal extracts, which demonstrates the efficiency of the extracts as antioxidants. Additionally, a sensorial analysis to the guacamoles was undertaken, and it was demonstrated that the participant`s favourite sauces were the ones containing algae. These results allow to conclude that brown macroalgae of the central region of Portugal contain numerous bioactive compounds that can promote, among other benefits, antioxidant and hypocholesterolemic activities. Hence, the incorporation of these seaweeds in a sauce that is already healthy will turn guacamole in a very promising functional food.